Analisis Beberapa Faktor yang Mempengaruhi Tingkat Suku Bunga Deposito dan Tabungan pada Bank Umum di Jawa Timur - Hendro P, Moch Aditya; Setiawati, Ririt Iriani Sri (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
The purpose of this study is to find out how many factors affect the rate of deposits and savings at commercial banks in East Java. This study uses secondary data for 15 years since 2001-2015 by using multiple linear regression analysis to determine the effect simultaneously and partially from Inflation variable, Gross Regional Domestic Product, Total Money Supply, Return On Assets to variable Interest Rate Deposit Rate And Savings as dependent variable. The results showed that simultaneously all the independent variables (X) affect the level of Deposits and savings. Partially variable of GRDP, JUB, ROA have an effect on significantly to deposit and saving interest rate while Inflation variable has no significant effect.